Kinetic recognition of the retinoblastoma tumor suppressor by a specific protein target - Chemes, Lucia Beatriz (2011)
The retinoblastoma tumor suppressor (Rb) plays a key role in cell cycle control and is linked to various types of human cancer. Rb binds to the LxCxE motif, present in a number of cellular and viral proteins such as AdE1A, SV40 large T-antigen and human papillomavirus (HPV) E7, all instrumental in revealing fundamental mechanisms of tumor suppression, cell cycle control and gene expression. A detailed kinetic study of RbAB binding to the HPV E7 oncoprotein shows that an LxCxE-containing E7 fragment binds through a fast two-state reaction strongly favored by electrostatic interactions. Conversely, full-length E7 binds through a multistep process involving a pre-equilibrium between E7 conformers, a fast electrostatically driven association step guided by the LxCxE motif and a slow conformational rearrangement. This kinetic complexity arises from the conformational plasticity and intrinsically disordered nature of E7 and from multiple interaction surfaces present in both proteins. Affinity differences between E7N domains from high- and low-risk types are explained by their dissociation rates. In fact, since Rb is at the center of a large protein interaction network, fast and tight recognition provides an advantage for disruption by the viral proteins, where the balance of physiological and pathological interactions is dictated by kinetic ligand competition. The localization of the LxCxE motif within an intrinsically disordered domain provides the fast, diffusion-controlled interaction that allows viral proteins to outcompete physiological targets. We describe the interaction mechanism of Rb with a protein ligand, at the same time an LxCxE-containing model target, and a paradigmatic intrinsically disordered viral oncoprotein.